1987
DOI: 10.1042/cs0730635
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral vascular responses during carotid baroreceptor stimulation in normotensive and hypertensive subjects

Abstract: 1. The carotid baroreceptors were stimulated for 2 min by neck suction at -30 and -60 mmHg in 19 normotensive subjects and 12 patients with moderate essential hypertension. 2. Blood pressure was measured with a mercury sphygmomanometer and heart rate was derived from beat-to-beat analysis of the electrocardiogram. Blood flow was measured simultaneously at calf and finger with venous occlusion plethysmography and the vascular resistance was calculated. 3. During neck suction at -30 and -60 mmHg there was a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
6
1
Order By: Relevance
“…However, the differences in protocols and narrower ranges of stimuli make direct comparisons with our study difficult. The results of our study contrast with the work of Duprez et al (1987) who reported that blood flow in the finger reduced significantly with neck suction, and Ernsting and Parry (1957) who noted a reduction in FBF with reduced pressure around the neck, but did not report the magnitude of this change. Lindblad et al (1982) showed changes in forearm vascular resistance (FVR) but it is difficult to assess the extent of the changes in FBF from their report.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…However, the differences in protocols and narrower ranges of stimuli make direct comparisons with our study difficult. The results of our study contrast with the work of Duprez et al (1987) who reported that blood flow in the finger reduced significantly with neck suction, and Ernsting and Parry (1957) who noted a reduction in FBF with reduced pressure around the neck, but did not report the magnitude of this change. Lindblad et al (1982) showed changes in forearm vascular resistance (FVR) but it is difficult to assess the extent of the changes in FBF from their report.…”
Section: Discussioncontrasting
confidence: 86%
“…However, others have reported reflex changes in peripheral vascular resistance or blood flow during stimulation of carotid sinus baroreceptors (Wallin et al 1975;Lindblad et al 1982;Ebert 1983;Victor and Mark 1985;Duprez et al 1987). Also, some workers have demonstrated an increase in the sensitivity of the carotid sinus baroreflex with reductions in CVP (Victor and Mark 1985;Pawelczyk and Raven 1989;Potts et al 1995) and a reduction in carotid sinus baroreflex sensitivity upon increases in CVP (Shi et al 1993).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Throughout each study period (about 12 min), the occlusion cuff placed on the ankle was kept inflated at supersystolic pressure (Ͼ240 mmHg) to impede the foot circulation. The foot has a rich skin vasculature, including arteriovenous anastomoses, which can be affected by changes in the level of arousal (which might be induced by NP and NS in the present study), whereas CBR itself has been reported to have little effect on the circulation in the distal portions of the extremities (3,4). Thus circulatory arrest in the foot should highlight the primary LVC and LBF responses elicited by CBR.…”
Section: Subjectsmentioning
confidence: 71%
“…However, the results of such investigations have been equivocal. Increases (Lindblad et al 1982), decreases (Ernsting & Parry, 1957;Duprez et al 1987;Ebert, 1982), or no change (Bevegard et al 1977;Escourrou et al 1993) in forearm blood flow or forearm vascular resistance have been reported during carotid sinus baroreceptor stimulation. The present study assessed forearm blood flow responses to a wide range of positive and negative pressures applied to the carotid sinus regions of the neck.…”
Section: School Of Biosciences University Of East London Romford Romentioning
confidence: 99%